2016
DOI: 10.1007/s40519-016-0353-x
|View full text |Cite
|
Sign up to set email alerts
|

Body dissatisfaction in adolescents with eating disorders

Abstract: This study contributes to highlight the idea of implementing effective prevention programs and specific interventions related to BD in the treatment of ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 58 publications
2
17
1
3
Order By: Relevance
“…Approximately 0.5% of adolescents are diagnosed with AN and 3% with BN, of whom 90 and 95% respectively are women [53]. In the present investigation, we found that the increase in BD was associated with an increased risk of developing ED, the risk being higher in girls than in boys, corroborating previous studies [54]. It should be noted that the present study was carried out away from the clinical environment, in adolescents who had not been diagnosed with ED; we found that 6.8% of our sample presented risk behaviors for developing ED.…”
Section: Discussionsupporting
confidence: 92%
“…Approximately 0.5% of adolescents are diagnosed with AN and 3% with BN, of whom 90 and 95% respectively are women [53]. In the present investigation, we found that the increase in BD was associated with an increased risk of developing ED, the risk being higher in girls than in boys, corroborating previous studies [54]. It should be noted that the present study was carried out away from the clinical environment, in adolescents who had not been diagnosed with ED; we found that 6.8% of our sample presented risk behaviors for developing ED.…”
Section: Discussionsupporting
confidence: 92%
“…As expected, RSES and CSES scores were lower in BN patients than in controls, reflecting that a frequent symptom of BN is body image dissatisfaction [37], which is linked to low self-esteem [38,39]. At the beginning of this study, we hypothesized that the RSES and CSES scores of BN patients would be associated with GMV alterations.…”
Section: Correlations Between Gmv Alterations and Clinical Variablesmentioning
confidence: 66%
“…Thompson et al 5 e van den Berg et al 3 destacam que identificar a influência da mídia, família e amigos na aparência corporal é importante para compreender a relevância desses contextos na internalização e comparação corporal das pessoas e, assim, conseguir intervir na insatisfação corporal. Essa intervenção poderá auxiliar na redução dos casos de transtornos de imagem e alimentação que causam prejuízos à saúde física e mental dos indivíduos 1,10,11 . No Brasil, as pessoas valorizam fortemente a aparência corporal, e isso é um dos principais fatores para a adoção de comportamentos de risco como, por exemplo, a restrição severa do consumo alimentar 12 .…”
Section: Cad Saúde Pública 2019; 35(3):e00179318unclassified